Association of proportion of the HDL-cholesterol subclasses HDL-2b and HDL-3 and macrovascular events among patients undergoing hemodialysis - Wen-Chin Lee (Nature Portfolio, 2021)
Abstract Altered high-density lipoprotein cholesterol (HDL-C) subclass distribution in hemodialysis (HD) patients is well documented. Aim of this study is to investigate the relationship between HDL-C subclass distribution and macrovascular events in patients undergoing HD. A total of 164 prevalent HD patients and 71 healthy individuals in one hospital-facilitated clinic were enrolled from May 2019 to July 2019 and individual HD patients was follow-up for one year. Macrovascular events (cerebral stroke, coronary heart disease) were recorded in the study period. The HDL-2b, HDL-3 proportions and biochemical parameters were measured. Pearson correlation test and logistic regression analysis were used to examine correlation and odds ratio (OR). 144 HD patients completed one-year follow-up. Cohort with macrovascular events revealed significantly lower HDL-2b and higher HDL-3 subclass proportions compared to those without events. By multivariable adjustment, HDL-3 subclass proportion revealed significantly increase risk for these events (OR 1.17, 95% CI 1.02–1.41, P = 0.044). HDL-2b subclass was significantly higher and HDL-3 subclass was significantly lower in the HD cohort under the hs-CRP level of < 3 mg/L compared to higher hs-CRP level. In conclusion, HDL-2b and HDL-3 subclasses distributions were associated with macrovascular events in HD patients. Proinflammatory status influences the distribution of HDL-2b and HDL-3 subclasses in HD patients.